Miller in Focus: New Perspectives in Hungarian Miller Studies: Mária Kurdi, ed. Arthur Miller öröksége: Centenáriumi írások műveiről [The Legacy of Arthur Miller: Centennial Writings about His Works]. AMERICANA eBOOKS, University of Szeged, 2015. ISBN: 978-615-5423-18-5 (.mobi); 978-615-5423- 19-2 (.epub); 978-615-5423-20-8 (PoD) - Szélpál, Lívia (FOCUS: Papers in English Literary and Cultural Studies, 2018)
-